Interested but not being served: mapping young people's participation in informal STEM education through an equity lens. Issue 2 (4th March 2022) - Godec, Spela; Archer, Louise; Dawson, Emily
ABSTRACT: It is commonly assumed that the reason many young people do not participate in informal STEM education (ISE) is because they lack interest in STEM. This paper draws on survey (n = 1, 624) and qualitative data (n = 36) with young people aged 11–14 to examine the ways in which science dispositions, demographic characteristics, 'consumption' of cultural practices and exclusion interact to produce unequal forms of STEM participation. Latent class analysis generated six groups within our quantitative dataset: three groups who infrequently participated in designed and community ISE practices ( Underserved Tech Enthusiasts, Underserved Creatives and Underserved Scientists), one group who only participated in specific forms of ISE practices ( Partly Served Generalists ) and two groups who frequently participated across a broad range of ISE practices ( Served Cultural Omnivores and Served STEMnivores) . Participation in ISE did not necessarily reflect young people's STEM interests; many minoritised young people reported being interested in STEM, yet rarely took part in designed and community ISE, while others from more socially advantaged backgrounds regularly participated regardless of their STEM interest. We conclude that ISE settings are excluding and failing to serve young people from minoritised backgrounds and there is a need to support these young people better.